(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2023)
This article describes methods of new ecological extraction of isoflavonoids from red clover flowers based on the use of deep eutectic solvents (NADES), consisting of citric acid and choline chloride are described, with simultaneous extraction of associated biologically active compounds. Data are given on. An analysis of the total polyphenols and antioxidants, including isoflavones, showed that NADES with a 30% water concentration was the most effective for extraction.